Cellular Basis for the Enhanced Efficacy of the Fms-Like Tyrosine Kinase 3 Ligand (FL) Adjuvanted VCG-Based Chlamydia abortus Vaccine - Richardson, Shakyra; Medhavi, Fnu; Tanner, Tayhlor; Lundy, Stephanie; Omosun, Yusuf; Igietseme, Joseph U.; Carroll, Darin; Eko, Francis O. (Frontiers in Immunology, 2021)
Efficacious vaccines are needed to control genital chlamydial diseases in humans and the veterinary industry. We previously reported a C. abortus (Cab) vaccine comprising recombinant Vibrio cholerae ghosts (rVCG) expressing the conserved and immunogenic N-terminal region of the Cab polymorphic membrane protein D (rVCG-Pmp18.1) protein that protected mice against intravaginal challenge. In this study, we investigated the immunomodulatory effect of the hematopoietic progenitor activator cytokine, Fms-like tyrosine kinase 3-ligand (FL) when co-administered with the rVCG-Pmp18.1 vaccine as a strategy to enhance the protective efficacy and the potential mechanism of immunomodulation. Groups of female C57BL/6J mice were immunized and boosted twice intranasally (IN) with rVCG-PmpD18.1 with and without FL or purified rPmp18.1 or rVCG-gD2 (antigen control) or PBS (medium) per mouse. The results revealed that co-administration of the vaccine with FL enhanced antigen-specific cellular and humoral immune responses and protected against live Cab genital infection. Comparative analysis of immune cell phenotypes infiltrating mucosal and systemic immune inductive tissue sites following immunization revealed that co-administration of rVCG-Pmp18.1 with FL significantly enhanced the number of macrophages, dendritic and NK cells,  and NK T cells in the spleen (systemic) and iliac lymph nodes (ILN) draining the genital tract (mucosal) tissues compared to rVCG-Pmp18.1 alone. Furthermore, FL enhanced monocyte infiltration in the ILN, while CD19+ B cells and CD4+ T cells were enhanced in the spleen. These results indicate that the immunomodulatory effect of FL is associated with its ability to mobilize innate immune cells and subsequent activation of robust antigen-specific immune effectors in mucosal and systemic lymphoid tissues.